La coopération entre concepteurs et tuteurs et l'évolution du rôle du tuteur dans un établissement unimodal d'enseignement à distance - Bruno Poellhuber; Martine Chomienne; Florent Michelot; Marie-Noëlle Fortin (Centre National d'Enseignement à Distance, 2017)
In distance education, a separation of roles between course design teams and student support teams are still characteristic of many specialized institutions. However, the role of the tutor has evolved considerably along with technological developments and the improvement of the quality of distance courses and student success requires a certain degree of cooperation between course design teams and tutors. The aim of this research is to describe the role of tutors as perceived by the different actors of the institution and to determine the state of cooperation between the course design teams and the student support teams. It is theoretically grounded in the social exchange theory and in the interprofessional cooperation model of St-Arnaud. An essentially qualitative case study was conducted based on individual and group interviews with four pedagogical advisors, six tutors and two administrative officers. The findings highlight significant differences between the role actually performed by tutors and the official role assigned to them. Regarding the nature of the interprofessional relation between tutors and course designers, the most frequent situation corresponds to a pression structure, but when the tutors play a role in the design process, the relationship tends to evolve towards a cooperation structure. Several measures have been implemented by the institution to encourage co-operation between these two groups of professionals and to increase the recognition of tutors contributions, but several challenges remain, notably with regard to the implementation of evaluation grids developed in a competency-based approach.